Detection of melting by in-situ observation of spherical-drop formation in laser-heated diamond-anvil cells - Pippinger, Thomas; Dubrovinsky, Leonid; Glazyrin, Kostantin; Miletich, Ronald; Dubrovinskaia, Natalia (Física de la Tierra, 2012)
A simple method for detection of melting event in laser-heated diamond anvil cells (DACs) is introduced. The melting is registered optically by the formation of spherical drops of the investigated material as heated in an inert pressure transmitting medium. Feasibility of the method is demonstrated on the examples of metal (iron and gold) and iron oxide (Fe2O3), materials molten at pressures over 40 GPa employing a portable laser heating system.